DsbA-L mediated renal tubulointerstitial fibrosis in UUO mice - Xiaozhou Li (Nature Portfolio, 2020)
DsbA-L upregulation prevents lipid-induced renal injury in diabetic nephropathy. Here, the authors show that DsbA-L knockout attenuates tubulointerstitial fibrosis in mice, and show that this occurs via activation of Smad3 and p53, which result in modulation of CTGF, a regulator of kidney fibrosis.